Enhanced Carotenoid Synthesis of Phormidium sp. in Stressed Conditions - Experimental Sciences, Editor (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Cyanobacteria, also known as blue-green algae or blue-green bacteria obtain their energy through photosynthesis. Phormidium, Filamentous unbranched, non nitrogen fixing, microscopic and later macroscopic up to several cm in diameter, usually covering substrates of different types. Phormidium sp. was selected for the experiment and grown in BG11 medium containing different concentration (0, 1, 2, 3, 4 µg/ml) after the growth period the cells were collected and used to estimate the amount of chlorophyll ‘a’, carotenoids, phycocyanin, free amino acids and proteins in different concentration. An increase in growth period days (0, 2, 4, 6, 8, 10) increase the cellular content namely chlorophyll ‘a’, carotenoids, phycocynin, free amino acids and proteins. Carotenoids are responsible for many of the red, orange and yellow hues of plant leaves, fruits, and flowers as well as the colors of some birds, insects, fish, and crustaceans. The carotenoid content showed positive increase by lowering the nitrogen concentration in which the modified BG11-A medium showed the highest value (85.2 µg/ml) in half strength. It is concluded that enhanced carotenoid synthesis in stressed conditions and it increases two ecological functions, providing photoprotection and increasing photosynthetic performance of surface cyanobacterial populations.